The impact of proposed tax, benefit and minimum wage reforms on household incomes and work incentives - James Browne (Institute for Fiscal Studies (IFS), 2015)
The UK government's proposed package of tax and benefit changes to be introduced between 2015-16 and 2019-20 (those announced in fiscal events up to and including the July Budget) will reduce household incomes by 455 a year on average. However, this average figure disguises considerable variation across the population. The biggest losers from these changes will be low-income households with children. Better-off households and pensioners will be less affected, or even gain from these changes. Low-income working households lose roughly the same as low-income non-working households from changes to the existing benefit system on average. However, this will change following the introduction of universal credit, as universal credit benefits some working households, in particular single-earner couples, but reduces the incomes of some non-working households. Cuts to out-of-work benefits will modestly strengthen work incentives on average. Two summary measures of the incentives for people to be in paid work, the participation tax rate and the replacement rate, fall by 2.5 percentage points(ppts) and 2.2ppts respectively. This is perhaps a smaller reduction than one might have expected given the scale of the benefit cuts. A key explanation for the limited effect these policies have on work incentives is the significant planned cuts to in-work support. Indeed, benefit changes other than universal credit increase participation tax rates for around 6.7 million people, and increase average participation tax rates among those groups who are more likely to receive tax credits while in paid work including lone parents and those whose partner is not in paid work. This arises because, for these individuals, in-work support is being cut by more than out-of-work benefits. Universal credit also strengthens work incentives on average, but in many ways has the opposite effect to other benefit changes. Whereas other benefit changes strengthen work incentives for those with a working partner but weaken them for those whose partner does not work, because universal credit increases the amount of support given to single-earner couples, it particularly strengthens work incentives for those whose partner is not in paid work. However, neither universal credit nor other benefit changes significantly strengthen work incentives for lone parents. [...]
Keywords: 330